Generalized choreoathetosis in an acquired immune deficiency syndrome patient with cerebral toxoplasmosis - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2008)
Many hypolkinetic and hyperkinetic movement disorders (e.g. parkinsonism, chorea, myoclonus, dystonia) are associated with acquired immune deficiency syndrome (AIDS) and may sometimes represent the initial manifestation of the illness. We described a 37-year-old human immunodeficiency virus (HIV)-infected patient with generalized choreoathetoid movements associated with AIDS. Cranial MRI revealed multiple cerebral and cerebellar abscesses. The diagnosis of toxoplasmosis was established by brain biopsy. Hemichorea and hemilballismus in AIDS patients are pathognomonic findings of cerebral toxoplasmosis. Generalized choreiforrn movement is a rare condition and related to the bilateral cerebral involvement in toxoplasma disease affecting the subcortical structures.
Keywords: AIDS; choreoathetosis; cerebral toxoplasma abscesses; MOVEMENT-DISORDERS; CHOREA; AIDS